Picazuro Pigeon Patagioenas picazuro (Aves: Columbidae), first confirmed record from Peru - Ugarte, Mauricio (2019)
In this note, I report an observation of one individual of Picazuro Pigeon, Patagioenas picazuro on the right bank of the Madre de Dios River in the Taricaya Ecological Reserve, 26 km northeast of Puerto Maldonado city, province of Tambopata, department of Madre de Dios. This observation is the first confirmed record of P. picazuro for Peru. The presence of P. picazuro in Peru could be due to deforestation and an increase of croplands in the study area.